Peningkatan Hasil Belajar Peserta Didik pada Pembelajaran IPAS Menggunakan Model Project Based Learning di Kelas V SDN 17 Manggis Ganting - Puspita, Sri Indah; Zuryanty, Zuryanty (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to describe the improvement of student learning outcomes in IPAS learning with the Project Based Learning model in class V SDN 17 Manggis Ganting Bukittinggi City. This type of research is a Classroom Action Research using qualitative and quantitative approaches. The research subjects were grade V students of SDN 17 Manggis Ganting Bukittinggi City as many as 19 students. Research data comes from observation, tests, and non-tests in the form of attitude and skills assessment of students.  The research was carried out as many as 2 cycles for cycle I, carried out as many as 2 meetings and cycle II as many as 1 meeting. In cycle I there was an increase in the completeness of learning outcomes by 81.57% and in cycle II it increased to 100%, the increase that occurred reached 18.43%.